2009
DOI: 10.1111/j.1439-0272.1993.tb02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of ofloxacin therapy in andrologic patients suffering from therapy-requiring asymptomatic infections

Abstract: In 1990, microbiological ejaculate analyses were carried out on a routine basis on 125 andrological patients, in addition to the determination of the concentration, motility and morphology of the spermatozoa. Fourteen patients (1 1.2%) with therapy-requiring asymptomatic infections (TAI) > lo4 CFU (colony-forming units) ml-' were effectively treated with Ofloxacin (TarividR) at 2 x 200 mg d-I for a period of 20 d. Concentration, motility and morphology of the spermatozoa were determined before the Ofloxacin tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…Degenerative changes in sperm supplemented with 0.5% PG in the present study were possibly due to an inhibition of phosphatase activity, decrease in membrane integrity of sperm, increase in peroxide radical generation, and depletion of antioxidant enzymes levels in semen following gentamicin incorporation as demonstrated in vitro by Andreessen et al. () and Narayana (). However, morphological damage of silver barb sperm in this study was possibly due to improper fixation prior to electron microscopy.…”
Section: Discussionsupporting
confidence: 69%
“…Degenerative changes in sperm supplemented with 0.5% PG in the present study were possibly due to an inhibition of phosphatase activity, decrease in membrane integrity of sperm, increase in peroxide radical generation, and depletion of antioxidant enzymes levels in semen following gentamicin incorporation as demonstrated in vitro by Andreessen et al. () and Narayana (). However, morphological damage of silver barb sperm in this study was possibly due to improper fixation prior to electron microscopy.…”
Section: Discussionsupporting
confidence: 69%
“…20 Anderson et al (2012) showed that Ofloxacin at a dose of 72 mg/kg per day had almost the highest potential in terms of impairment of the rat testicular function. 24 Other studies also added that fluoroquinolones have toxic effects on testicular functions of different animals .21,25-28…”
Section: Discussionmentioning
confidence: 99%
“…Лечение ХП, сопровождающегося патоспермией, является еще более сложной задачей, поскольку длительные курсы антибактериальной терапии и использование ряда других средств патогенетической терапии могут вести к еще большему ухудшению показателей оплодотворяющей способности спермы. В современной литературе доступен ряд экспериментальных и клинических исследований, в которых продемонстрировано негативное влияние антибактериальных препаратов на сперматогенез [16,17]. Именно поэтому для лечения подобной категории пациентов необходимо использование лекарственных средств, позволяющих купировать воспалительный процесс в предстательной железе, улучшить физикохимические и биохимические характеристики секрета простаты и в то же время оказывающих позитивное влияние на сперматогенез.…”
Section: Introductionunclassified